Optically Reconfigurable Chiral Microspheres of Self-Organized Helical Superstructures with Handedness Inversion - Wang, Ling (Mater Horiz, 2017)
Optically reconfigurable monodisperse chiral microspheres of self-organized helical superstructures with dynamic chirality were fabricated via a capillary-based microfluidic technique. Light-driven handedness-invertible transformations between different configurations of microspheres were vividly observed and optically tunable RGB photonic cross-communications among the microspheres were demonstrated.